A Study on Intercultural Contact Factors and Acculturation: a Survey of African Merchants in Guangzhou - WU, Yiming; GAO, Wenjing (Advances in Social Sciences Research Journal, 2020)
This paper adopted a qualitative study of questionnaires to identity how selected intercultural contact factors are correlated with psychological and sociocultural adaptation. It is found that psychological and sociocultural adaptation situations of African merchants in Guangzhou are both moderately well;psychological adaptation of African merchants was proved to be correlated with 5 intercultural contact factors.; the sociocultural adaptation of African merchants was proved to be correlated with 5 intercultural contact factors;correlation analysis proved that outgroup social support has a stronger positive correlation with both psychological and sociocultural adaptation than ingroup social support, which is the main source of social support for African merchants;the overlapping and strength differences of correlations show that the two acculturation dimensions of African merchants are distinct and interrelated, thus verified the Colleen Ward's two-dimension acculturation model in the group of African merchants in Guangzhou.